Investigations on properties of Mg-Al2O3 composites fabricated via stir casting route. (2020) - Kumar, S. Dinesh; Ravichandran, M.; Meignanamoorthy, M.; Sakthivelu, S.; Alagarsamy, S.V.; Chanakyan, C.
Abstract: Magnesium metal matrix composites are extremely attractive for application of light and strong materials in various industries. In the present work, Magnesium matrix composites reinforced by Al2 O3 with different weight percent of particles were synthesized and fabricated by means of Stir casting process. The property of Al2 O3 particle content with different weight percent of particles on the mechanical properties of the composites such as density, porosity, hardness and tensile strength were investigated. The microstructures of magnesium metal matrix composites were studied using scanning electron microscope. It showed the uniform distribution of Al2 O3 in Mg metal matrix composites and bonded to the composites. The results show that the hardness and the tensile strength of the composites increased with increasing weight fraction of Al2 O3 particles.